Application of the Adat Principles Barenti ko Syara’, Syara’ Barenti ko Kitabullah in Sumbawa Regency (International Journal of Scientific Research and Management (IJSRM), 2023)
The existence of indigenous peoples has been regulated in Article 18B paragraph (2), which states that the state recognises and respects customary law community units and their traditional rights as long as they are still alive and by development. Society and the principles of the unitary state of the Republic of Indonesia are further regulated in law to provide recognition and respect for customary law communities as a basic concept or pillar of the application of customary law in Indonesia. There is much evidence of traces of the spread of Islam left by their ancestors, both in ancient manuscripts, historical buildings, customs, arts, and various other cultural products, including in the Sumbawa district, which until now apply established principles in everyday life. The regional regulation establishes a traditional institution as a body or institution whose job is to preserve customs in Sumbawa which have been ingrained and rooted in the life of the Sumbawa people, accommodating businesses such as customs for marriage, inheritance, land management, and several other customary norms which have the motto of the Adat principle. Barenti ko syara’, syara’ barenti ko kitabullah.